A nationwide register-based study of the prevalence of burning mouth syndrome in Taiwan from 2004 to 2013 - Ni-Yu Su; Yu-Hsun Wang; Yu-Chao Chang (Elsevier, 2021)
Background/purpose: Burning mouth syndrome (BMS) is defined as a chronic burning pain of the oral mucosa with no associated clinical signs or apparent extraneous cause. Limited epidemiologic data have been published. In this study, we probed the nationwide registered database to assess the prevalence of BMS in Taiwan. Materials and methods: A retrospective study was conducted to analyze the dental dataset compiled by the Taiwan's National Health Insurance Research Database from 2004 to 2013. The diagnosis of BMS was identified in accordance with the International Classification of Disease, Ninth revision. In addition, sex and age were analyzed by multivariate Poisson regression. Results: The prevalence of BMS revealed from 2.24 (per 104) to 3.11 (per 104) over past 10 year period. Female has higher risk of BMS than male (RR: 1.39; 95% CI: 1.37-1.41). The 50-59 years old group, 60-69 years old group, and >70 years old group had 1.55-, 2.06-, and 2.58-fold risk than 40-49 years old group for BMS (p < 0.001), respectively. Conclusion: Taken together, this is the first reported nationwide population based prevalence data for BMS in Taiwan. The risk for BMS is highly associated with female and advancing age.